Association of Osteoporosis with Tooth Loss and Dental Radiomorphometric Indices - Anna Damanaki; Marie Luis Habel; James Deschner (Biomedicines)
Background/Objectives: Osteoporosis is a systemic disease associated with reduced bone mass, impaired bone microarchitecture, and thus an increased risk of bone fractures. Moreover, patients with osteoporosis are more likely to experience periodontal diseases and tooth loss. Some indices have been proposed to detect osteoporosis on dental panoramic radiographs. The aim of our retrospective study was to investigate the association between osteoporosis and the loss of alveolar bone and teeth and to evaluate the validity of several dental radiomorphometric indices for assessing osteoporosis. Methods: In patients with and without osteoporosis, tooth loss, alveolar bone loss, the panoramic mandibular index (PMI), mental index (MI), and mandibular cortical index (MCI) were determined. Results: Compared with the non-osteoporotic group, patients with osteoporosis showed more tooth loss and more severe alveolar bone loss. PMI and MI were lower in patients with osteoporosis than in the non-osteoporotic group. Analysis of MCI showed that category C3 (cortical layer forms strong endosteal cortical residues and is clearly porous) was significantly more common in patients with osteoporosis. Conclusions: Osteoporosis is associated with more tooth and alveolar bone loss. Furthermore, various dental radiomorphometric indices are altered in osteoporosis and could thus help to better assess osteoporosis of the jaw.